Can a new role, the (Trainee) Associate Psychological Practitioner (T/APP), add value in General Practice? Results from the pilot year evaluation. (29th September 2022) - Budd, Miranda; Gardner, Rebecca; Bhutani, Gita; Gardner, Kathryn; Iqbal, Ameera; Harding, Charlotte; Baguley, Clare; Chauhan, Umesh
Abstract: Background: The deployment of (Trainee) Associate Psychological Practitioners (T/APPs) to deliver brief psychological interventions focusing on preventing mental health deterioration and promoting emotional wellbeing in General Practice settings is a novel development in the North West of England. As the need and demand for psychological practitioners increases, new workforce supply routes are required to meet this growth. Aims: To evaluate the clinical impact and efficacy of the mental health prevention and promotion service, provided by the T/APPs and the acceptability of the role from the perspective of the workforce and the role to T/APPs, patients and services. Methods: A mixed-methods design was used. To evaluate clinical outcomes, patients completed measures of wellbeing (WEMWBS), depression (PHQ-9), anxiety (GAD-7) and resilience (BRS) at the first session, final session and at a 4–6 week follow-up. Paired-samples t-tests were conducted comparing scores from session 1 and session 4, and session 1 and follow-up for each of the four outcome measures. To evaluate acceptability, questionnaires were sent to General Practice staff, T/APPs and patients to gather qualitative and quantitative feedback on their views of the T/APP role. Quantitative responses were collated and summarised. Qualitative responses were analysed using inductive summative content analysis to identify themes. Results: T-test analysis revealed clinically and statistically significant reductions in depression and anxiety and elevations in wellbeing and resiliency between session 1 and session 4, and at follow-up. Moderate–large effect sizes were recorded. Acceptability of the T/APP role was established across General Practice staff, T/APPs and patients. Content analysis revealed two main themes: positive feedback and constructive feedback. Positive sub-themes included accessibility of support, type of support, patient benefit and primary care network benefit. Constructive sub-themes included integration of the role and limitations to the support. Conclusions: The introduction of T/APPs into General Practice settings to deliver brief mental health prevention and promotion interventions is both clinically effective and acceptable to patients, General Practice staff and psychology graduates.